2016
DOI: 10.1038/nmicrobiol.2016.191
|View full text |Cite|
|
Sign up to set email alerts
|

Secreted tryptophanyl-tRNA synthetase as a primary defence system against infection

Abstract: The N-terminal truncated form of a protein synthesis enzyme, tryptophanyl-tRNA synthetase (mini-WRS), is secreted as an angiostatic ligand. However, the secretion and function of the full-length WRS (FL-WRS) remain unknown. Here, we report that the FL-WRS, but not mini-WRS, is rapidly secreted upon pathogen infection to prime innate immunity. Blood levels of FL-WRS were increased in sepsis patients, but not in those with sterile inflammation. FL-WRS was secreted from monocytes and directly bound to macrophages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
94
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(111 citation statements)
references
References 34 publications
11
94
2
Order By: Relevance
“…Trp supplementation, a condition that promotes the accumulation of Trp metabolites, reduced WARS expression (Figure 3A), while not affecting WARS2 (Figure 3B). Conversely, Trp starvation induced WARS mRNA (Figure 3C) in cell lines with high (A172) and medium (LN18) TDO2 expression, high IDO1 expression (SKOV3) as well as in cells that do not express any Trp-degrading enzymes (LN229) 16,20 . The increase in WARS mRNA upon Trp starvation also translated into increased WARS protein levels as assessed in LN229 glioblastoma cells.…”
Section: Resultsmentioning
confidence: 99%
“…Trp supplementation, a condition that promotes the accumulation of Trp metabolites, reduced WARS expression (Figure 3A), while not affecting WARS2 (Figure 3B). Conversely, Trp starvation induced WARS mRNA (Figure 3C) in cell lines with high (A172) and medium (LN18) TDO2 expression, high IDO1 expression (SKOV3) as well as in cells that do not express any Trp-degrading enzymes (LN229) 16,20 . The increase in WARS mRNA upon Trp starvation also translated into increased WARS protein levels as assessed in LN229 glioblastoma cells.…”
Section: Resultsmentioning
confidence: 99%
“…The MSC protein AIMP1 also has a critical role in innate and adaptive antiviral immunity against influenza A virus infection [21]. In addition, secreted WRS acts as an early warning signal of host infections [22]. Together, these findings suggest that ARSs may act as cellular sensors as well as immunoregulators in the context of infection.…”
Section: Introductionmentioning
confidence: 98%
“…Recent studies identified novel molecular and cellular processes through which ARSs control host immune responses against infections [20][21][22]. EPRS contributes to innate antiviral immunity and promotes viral clearance [20].…”
Section: Introductionmentioning
confidence: 99%
“…28 Interestingly, the activity of the FL-TrpRS can be recapitulated by the N-terminal 154 residues, which contain the WHEP domain and the ESE (Fig. 1A).…”
Section: Discussionmentioning
confidence: 98%